A memória episódica e a imaginação episódica: uma abordagem da distinção dos estados mentais mediante tarefas cognitivas - Richter, Bruna Natalia (2024)
Cognitive studies demonstrate a significant overlap between the processes of episodic memory and episodic imagination, challenging theories that seek to differentiate them. Faced with this similarity, two main perspectives emerge: one that considers them as distinct capacities and one that unifies them into a common cognitive system. In this work, I defend the first perspective, proposing that cognitive tasks play a crucial role in distinguishing between the two. The task, shaped by the context and stimuli, acts as a guide, directing the mental process towards the retrieval of past experiences (episodic memory) or the construction of new experiences (episodic imagination). By introducing the concept of cognitive task as a determining factor, this study contributes to a more refined understanding of the relationship between memory and imagination, aligning with the discontinuous perspective that emphasizes the distinction between these processes.